Pengaruh Pendidikan Kewirausahaan Pada Minat Berwirausaha Mahasiswa PTKIN di Provinsi Lampung - Fitria, Sela Nur; Nasruddin, Nasruddin; Anggraeni, Erike (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
This abstract section provides a brief summary of the contents of the paper, the main objectives of the study, the methods used, the results obtained and the main conclusions. The number of unemployed people in Indonesia is relatively high, including in Lampung province. Moreover, by the year 2030, there will be a demographic bonus, where the productive age group will reach 64% of the total population, making it necessary to cultivate young entrepreneurs to face this situation. Universities can play a role in increasing the number of entrepreneurs through Entrepreneurship Education by offering entrepreneurship courses. The aim of this research is to determine the influence of entrepreneurship education on students' entrepreneurial interest. This study was conducted in all Islamic State Universities in Lampung province using a quantitative research method with a questionnaire as the data collection instrument. The sample consisted of 90 students who were enrolled in entrepreneurship courses. The results showed that entrepreneurship education affects student entrepreneurial interest. This is indicated by the value of tcount> ttable (5.709> 1.66196) and the coefficient of determination of 0.334 (r square of 0.334 or 33.4%). So that the more optimal entrepreneurship education, the more interest in student entrepreneurship will increase by 33.4%.